HiatoGast 1: An exploring, semiblinded trial establishing a new endoscopical categorisation of axial hiatal hernias - Eckhardt, Daniel; Engel, Matthias; Golcher, Henriette; Krautz, Christian; Grützmann, Robert; Elshafei, Moustafa (BMJ Global Health, 2019)
Introduction Axial hiatal hernias are a common incidental finding in endoscopical examinations, but reflux symptoms do not necessarily correspond to the presence of hiatal hernias. Diagnosing a reflux disease is difficult due to a leak of existing distinct criteria, especially in order to evaluate a surgical indication. Also a preoperative measurement of the hernia is necessary to choose between surgical options. Methods and analysis We planned a semiblinded trial including a questionnaire and an oesophagogastroduodenoscopy afterwards. While the endoscopy is done, the hiatus oesophagi should be measured in inversion technique under maximum insufflation including length, width and herniated volume. A sample of 210 participants until December 2020 is determined to evaluate the primary endpoint: we look forward to evaluate the anatomical parameters of reflux and non-reflux participants. Ethics and Dissemination The study has been approved by the local ethics committee on 12th February 2019, the data will bei published after closure of inclusion. Trial registration number German Clinical Trials Register (DRKS00016863).
CRIS-Team Scopus Importer:2019-07-02
Keywords: endoscopical technique; gastroscopy; hiatal hernia; reflux